The scrotal lump that you can't get above: A case report of a spermatic cord dermoid cyst mimicking an incarcerated inguinal hernia - Ali Hooshyari; David Scholtz; Flavio Vasconcelos Ordones; Lodewikus Petrus Vermeulen (Urology Case Reports, 2023)
A 24-year-old healthy male with left sided groin pain and swelling extending into the left hemiscrotum. Computed tomography reported an encysted spermatic cord hydrocoele. Open exploration revealed a cystic structure arising from the spermatic cord. Histopathological analysis demonstrated sebaceous glands within the wall of the cyst, pathognomonic for a dermoid cyst. A literature review demonstrates just 12 cases of inguinal dermoid cysts to date. Our case demonstrates the importance of radiological imaging in cases of groin lumps to facilitate surgical planning as well as the importance of sending surgical specimens for histopathological analysis to aid in the event of recurrence.